Breast carcinoma among patients undergoing breast ultrasonography in a tertiary care center: A descriptive cross-sectional study - Guragain, Seema; Mandal, Sandip Kumar; Gnawali, Suman; Panday, Shailesh; Sharma, Nitu; Adhikari, Ganga D; Yadav, Ajay Kumar (Nepalese Journal of Cancer, 2023)
Introduction: Ultrasonography (USG) is one of the modality of choice for detection of breast lesions due to its advantage over radiation exposure, differentiation between solid tumor and cyst filled with fluid, especially for imaging of young age females. The aim of the study is to find out the prevalence of breast cancer among the patients undergoing scanning of USG and estimate its sensitivity, specificity and accuracy to detect breast lesion in comparison with histopathology.Materials and Methods: A descriptive cross-sectional study was conducted from 15th April to 10th September, 2022. A sample size of 426 was taken in convenience sampling method. Collected data were entered and analyzed on SPSS 25.0. Sensitivity, specificity and accuracy of USG to detect breast lesion in comparison to histopathology findings.Results: Among 426 patients sample coming from OPD, breast cancer was seen in 53 (12.44%) patients. Among 426, 418 were female and 8 were male patients. Age ranged from 13-75 years. The sensitivity, specificity, negative predictive value, positive predictive value and accuracy of USG to detect breast lesion are 94%, 100%, 94.23%, 100% and 97% respectively.Conclusion: The sensitivity, specificity, negative predictive value, positive predictive value and accuracy of USG to detect breast lesion is quite high. USG is highly recommended in examination of breast lesions.